2014
DOI: 10.1002/qj.2406
|View full text |Cite
|
Sign up to set email alerts
|

Weakly nonlinear Prandtl model for simple slope flows

Abstract: The Prandtl model couples, probably in the most succinct way, basic boundary-layer dynamics and thermodynamics for pure anabatic and katabatic flows over inclined surfaces by assuming a one-dimensional steady-state balance between buoyancy and turbulent friction. Although the classic Prandtl model is linear, having an a priori assigned vertically constant eddy diffusivity and heat conductivity, K, in this analytic work we partly relax both of these restrictions. The first restriction is loosened by using a wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 74 publications
(130 reference statements)
1
47
0
Order By: Relevance
“…This study is independent but based on the work of Grisogono et al (2015). There it was shown that with the weakly nonlinear Prandtl model one obtains solutions with stronger near-surface stratification and weaker katabatic wind speed (with both constant and variable eddy heat conductivity).…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…This study is independent but based on the work of Grisogono et al (2015). There it was shown that with the weakly nonlinear Prandtl model one obtains solutions with stronger near-surface stratification and weaker katabatic wind speed (with both constant and variable eddy heat conductivity).…”
Section: Introductionmentioning
confidence: 98%
“…This paper starts with the classical theoretical model of slope flows developed by Prandtl (1942), somewhat modified and verified by Defant (1949), who deployed it specifically for anabatic flow (see also Zardi and Whiteman, 2013), and an extended Prandtl model that includes weakly nonlinear effects as done in Grisogono et al (2015). It includes the standard concepts of potential, kinetic and total energy, now for katabatic and anabatic flows.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations